Long-range energy transport in single supramolecular nanofibres at room temperature - Haedler, Andreas T.; Kreger, Klaus; Issac, Abey; Wittmann, Bernd; Kivala, Milan; Hammer, Natalie; Koehler, Juergen; Schmidt, Hans-Werner; Hildner, Richard (Nature, 2015)
Efficient transport of excitation energy over long distances is a key process in light-harvesting systems, as well as in molecular electronics. However, in synthetic disordered organic materials, the exciton diffusion length is typically only around 10 nanometres (refs 4, 5), or about 50 nanometres in exceptional cases, a distance that is largely determined by the probability laws of incoherent exciton hopping. Only for highly ordered organic systems has the transport of excitation energy over macroscopic distances been reported–for example, for triplet excitons in anthracene single crystals at room temperature, as well as along single polydiacetylene chains embedded in their monomer crystalline matrix at cryogenic temperatures (at 10 kelvin, or -263 degrees Celsius). For supramolecular nanostructures, uniaxial long-range transport has not been demonstrated at room temperature. Here we show that individual self-assembled nanofibres with molecular-scale diameter efficiently transport singlet excitons at ambient conditions over more than four micrometres, a distance that is limited only by the fibre length. Our data suggest that this remarkable long-range transport is predominantly coherent. Such coherent long-range transport is achieved by one-dimensional self-assembly of supramolecular building blocks, based on carbonyl-bridged triarylamines, into well defined H-type aggregates (in which individual monomers are aligned cofacially) with substantial electronic interactions. These findings may facilitate the development of organic nanophotonic devices and quantum information technology.
EAM Import::2019-03-12